Rural women and ecotourism: Modeling entrepreneurial behavior in Iran - Sahar Aghdasi; Maryam Omidi Najafabadi; Seyed Jamal Farajallah Hosseini (Journal of Innovation and Entrepreneurship, 2023)
Fars province, as one of the most susceptible ecotourism regions of Iran, has paid attention to the establishment of ecotourism residences with the priority of rural women through ecotourism entrepreneurial training in recent years. In this regard, the present study investigates the effective factors on entrepreneurial behavior with Fars rural women ecotourism approach in Iran. The participants of the study were 431 of rural women in Fars and 205 were decided by Cochran formula. It is inferred from the results that step-by-step procedure of changing norms towards the acceptance of rural women entrepreneurs as well as the acceptance of ecotourism culture through the establishment of local and regional institutions and organizations in a context of family support with strong bonds of commitment, solidarity, environmental and infrastructural foundations will lead to a strong desire to constitute ecotourism residence by rural women.
Keywords: 650; Entrepreneurial attitude; Entrepreneurial behavioral; Entrepreneurial intention; Rural women; Tourism development